A Required Ophthalmology Rotation: Providing Medical Students with a Foundation in Eye-Related Diagnoses and Management - Eve M.R. Bowers; Brittany Perzia; Rikki Enzor; Owen Clinger; Sanya Yadav; Patrick W. Commiskey; Peter Mortensen; Evan Waxman (Association of American Medical Colleges, 2021)
Introduction Current ophthalmologic training in medical school is inadequate in preparing medical students to handle basic eye complaints as nonophthalmology residents. Most medical students are uncomfortable performing eye examinations, but increased ophthalmology training improves confidence in this area. The University of Pittsburgh School of Medicine (UPSOM) teaches students the basics of ophthalmology with a required 1-week rotation during the 1-month specialty care clerkship (SCC), providing students with skills to perform rudimentary eye examinations as nonophthalmology providers. Methods Within a 1-week ophthalmology rotation, we developed a series of interactive case-based teaching sessions, handouts, and homework that accompanied clinical instruction to familiarize third- and fourth-year medical students with ophthalmic equipment, terminology, diagnosis, and management. Of learners, 67 (roughly 11 per cohort) rotated on six consecutive SCCs beginning in May 2019. All learners completed an in-house exam and received resident clinical evaluations at the end of their rotation. Results Of the 64 participants who responded to the survey, 100% rated the quality of teaching sessions outstanding or good, and 83% of students strongly agreed or agreed with the statement, "I believe the overall teaching in the ophthalmology clinical settings was good quality." The average clinical and exam score for ophthalmology over 6 months was 4.5 out of 5, and 83% respectively. Discussion Generally positive student feedback as well as high clinical and exam scores suggested that the required UPSOM ophthalmology clerkship was both engaging and effective. This course can be easily adapted to teach students at other medical institutions.